upramolecular complex based on MWNTs/Boltorn H40 provides fast response to a Sandwich-type amperometric lactate biosensor - Romero, Marcelo Ricardo (2017)
Most sandwich-type biosensors can be used several times, since their long-time stability generally ranges from weeks to several months. However, the response-time of this kind of sensors is typically slow because reagents and products have to diffuse through filtering membranes and the enzymatic matrix. In this manuscript, multiwalled carbon nanotubes (MWNTs) have been used for wiring the enzymatic matrix to the electrode surface. To achieve this, the hyperbranched polymer Boltorn H40 (BH40) has been self-assembled at the surface of MWNTs. After the assembling, the suspension of BH40-MWNTs became stable and its functionality was tested by replacing mucin in the enzymatic matrix of a previously reported sandwich-type lactate biosensor. The inclusion of BH40-MWNTs in the biosensor: increased the diffusion coefficient of soluble species by decreasing the elastic properties of the enzymatic matrix, kept the characteristics of the microenvironment where the enzyme is stored, and wired the enzymatic matrix through a 13 μm thick polycarbonate membrane to the electrode surface. It is important to understand that the superstructure of BH40-MWNTs does not increase the active surface of the electrode. Instead of this, it is a conductive 3D network that connects the enzymatic matrix to the electrode. As a result, the response-time of this novel sandwich-type lactate biosensor is much shorter than that of conventional biosensors because the mediator of the enzyme (oxygen) can be regenerated at the enzymatic matrix and it does not have to diffuse to the electrode surface.